ORGANIZATION OF PRIMARY PROFESSIONAL AND PSYCHOLOGICAL ADAPTATION OF YOUNG UNIVERSITY PROFESSORS - Ashot R. Alaverdov; Tatiana P. Alaverdova (Moscow Polytechnic University, 2016)
The article discusses the strategy and tactics of managing the development of young university professors recruited for a permanent job in higher education institutions. The authors outline the key problems arising during the period of their professional and psychological adaptation. One of the main problems is a low efficiency of a new generation of teaching staff. Therefore University HR-policy should formulate strategic goals and approaches of primary development of young professors. Particular attention is paid to the role of personal supervisors and from among the most experienced professors of a department. The authors offer to use special control and evaluation procedures including public attestation to confirm the successful completion of professional and psychological adaptation process of an intern.